A Monolithic High-G SOI-MEMS Accelerometer for Measuring Projectile Launch and Flight Accelerations. (2006) - Davis, Bradford S.; Denison, Tim; Kuang, Jinbo
Abstract : Analog Devices (ADI) has designed and fabricated a monolithic high-g acceleration sensor (ADXSTC3-HG) fabricated with the ADI silicon-on-insulator micro-electro-mechanical system (SOI-MEMS) process. The SOI-MEMS sensor structure has a thickness of 10 um, allowing for the design of inertial sensors with excellent cross-axis rejection. The high-g accelerometer discussed in this paper was designed to measure in-plane acceleration to 10, 000 g while subjected to 100, 000 g in the orthogonal axes. These requirements were intended to meet Army munition applications. The monolithic sensor was packaged in an 8-pin leadless chip carrier (LCC-8) and was successfully demonstrated by the US Army Research Laboratory (ARL) as part of an inertial measurement unit during an instrumented flight experiment of artillery projectiles launched at 15, 000 g.